Comparison of TB-LAMP, GeneXpert MTB/RIF and culture for diagnosis of pulmonary tuberculosis in The Gambia - Bojang, Adama L.; Mendy, Francis S.; Tientcheu, Leopold D.; Otu, Jacob; Antonio, Martin; Kampmann, Beate; Agbla, Schadrac; Sutherland, Jayne S. (The Journal of infection, 2016)
Diagnosis of tuberculosis (TB) remains difficult, particularly in resource-limited settings. The development of nucleic acid-based tests for detection of Mycobacterium tuberculosis complex (MTBC) has significantly increased sensitivity compared to conventional smear microscopy and provides results within a matter of hours compared to weeks for the current gold-standard, liquid culture. In this study we performed side-by-side comparison of mycobacterial detection assays on sputum samples from 285 subjects presenting with symptoms suggestive of TB in The Gambia and a cross-sectional cohort of 156 confirmed TB patients with a median of 2 months of treatment. A novel assay, Loop-Mediated Amplification test for TB (TB-LAMP), was compared to smear microscopy, MGIT culture and GeneXpert MTB/RIF for all samples. When culture was used as the reference standard, we found an overall sensitivity for TB-LAMP of 99% (95% CI: 94.5–99.8) and specificity of 94% (95% CI: 89.3–96.7). When latent class analysis was performed, TB-LAMP had 98.6% (95% CI: 95.9–100) sensitivity and 99% (95% CI: 98.2–100) specificity compared to 91.1% (95% CI: 86.1–96) sensitivity and 100% (95% CI: 98.2–100) specificity for MGIT culture. GeneXpert had the highest sensitivity 99.1% (95% CI: 97.1–100) but the lowest specificity 96% (95% CI: 92.6–98.3). Both TB-LAMP and GeneXpert showed high sensitivity and specificity regardless of age or strain of infection. Our findings show the diagnostic utility of both GeneXpert and TB-LAMP in The Gambia. Whilst TB-LAMP requires less infrastructure, it is unable to detect drug-resistant patterns and therefore would be most suitable as a screening test for new TB cases in peripheral health clinics. •Use of a novel TB diagnostic test in a laboratory setting was determined.•TB-LAMP was comparable to GeneXpert but required less infrastructure.•High sensitivity and specificity for diagnosis of TB.•Usefulness as a screening assay for TB in developing country settings.